Respuestas
Respuesta dada por:
3
Respuesta:
a) 15
Explicación paso a paso:
-{3 – [3 – (3x – 2)] + 5} = 12 – 4x
-{3 – [3 – 3x + 2] + 5} = 12 – 4x
-[3 – (5- 3x )+ 5] = 12 – 4x
-(3 – 5+3x + 5) = 12 – 4x
-(3+3x)=12-4x
-3-3x=12-4x
-3-12=3x-4x
-15= -x
15=x
Respuesta dada por:
3
Respuesta:
15
Explicación paso a paso:
-(3-(3-3x+2)+5)=12-4x
-(3-(5-3x)+5)=12-4x
-(3-5+3x+5)=12-4x
-(3+3x)=12-4x
-3-3x=12-4x
-3x+4x=12+3
x=12+3
x=15
Preguntas similares
hace 5 años
hace 5 años
hace 8 años
hace 8 años
hace 9 años
hace 9 años